2012
DOI: 10.1007/s10933-012-9647-9
|View full text |Cite
|
Sign up to set email alerts
|

A 100-year record of changes in organic matter characteristics and productivity in Lake Bhimtal in the Kumaon Himalaya, NW India

Abstract: Sediment variables total organic carbon (TOC), total nitrogen (TN), total sulfur (TS), as well as their accumulation rates and atomic ratios (C/N and C/S), were studied along with stable isotopes (δ 13 C, δ 15 N, and δ 34 S), and specific biomarkers (n-alkanes and pigments) in a 35-cm-long sediment core from Lake Bhimtal, NW India. The average sedimentation rate is 3.6 mm yr -1 , and the core represents a provisional record of 100 years of sedimentation history. Bulk elemental records and their ratios indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…The study of Choudhary et al (2013) found an average sedimentation rate of 3.6 mm/year for a sediment core (35 cm) from the Lake Bhimtal, NW India with a provisional 100 years of sedimentation history. The data on total organic carbon (TOC), total nitrogen (TN), total sulfur (TS), stable isotopes (δ 13 C, δ 15 N and δ 34 S), and specific biomarkers (n-alkanes and pigments) indicated an increase in primary productivity as a result of the change in trophic state correlating temporally with the increase in anthropogenic activities.…”
Section: Sediment Geochemistry As Paleoclimate Proxymentioning
confidence: 99%
See 4 more Smart Citations
“…The study of Choudhary et al (2013) found an average sedimentation rate of 3.6 mm/year for a sediment core (35 cm) from the Lake Bhimtal, NW India with a provisional 100 years of sedimentation history. The data on total organic carbon (TOC), total nitrogen (TN), total sulfur (TS), stable isotopes (δ 13 C, δ 15 N and δ 34 S), and specific biomarkers (n-alkanes and pigments) indicated an increase in primary productivity as a result of the change in trophic state correlating temporally with the increase in anthropogenic activities.…”
Section: Sediment Geochemistry As Paleoclimate Proxymentioning
confidence: 99%
“…Total organic carbon (TOC) and total nitrogen (TN) have been used to understand the source of organic carbon (Choudhary et al, 2013;Agrawal et al, 2015). Source of carbon can be identified using 14 C, 12 C, 13 C isotopes.…”
Section: Weathering Of Rocks Controls the Mineralogy And Composition mentioning
confidence: 99%
See 3 more Smart Citations